1991
DOI: 10.1083/jcb.115.2.505
|View full text |Cite
|
Sign up to set email alerts
|

A plasma membrane protein is involved in cell contact-mediated regulation of tissue-specific genes in adult hepatocytes.

Abstract: . We have identified the liver-regulating protein (LRP), a cell surface protein involved in the maintenance of hepatocyte differentiation when cocultured with rat liver epithelial cells (RLEC) . LRP was defined by immunoreactivity to a monoclonal antibody (mAb L8) prepared from RLEC. mAb L8 specifically detected two polypeptides of 85 and 73 kD in immunoprecipitation of both hepatocyte-and RLECiodinated plasma membranes . The involvement of these polypeptides, which are integral membrane proteins, in cell inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 56 publications
3
51
0
Order By: Relevance
“…The mechanisms by which non-parenchymal cells allow sustained expression of differentiated functions of hepatocytes in co-cultures are not fully understood, although a key plasma membrane protein involved in hepatocyte-rat-liver-epithelialcell recognition in co-cultures has been identified (Corlu et al, 1991). Nevertheless, this culture model remains one of the most powerful and useful systems to study the effects of drug exposure over several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which non-parenchymal cells allow sustained expression of differentiated functions of hepatocytes in co-cultures are not fully understood, although a key plasma membrane protein involved in hepatocyte-rat-liver-epithelialcell recognition in co-cultures has been identified (Corlu et al, 1991). Nevertheless, this culture model remains one of the most powerful and useful systems to study the effects of drug exposure over several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated cell surface proteins in epithelial-nonparenchymal interactions in hepatocyte cocultures. 17,18 Our gene expression profiling yielded Delta-like homolog 1, whose expression profile correlated positively (i.e., high-medium-low) with the ability of fibroblasts to induce functions in hepatocytes. Delta-like homolog 1 belongs to the epidermal growth factor-like homeotic protein family that includes proteins such as the Notch receptor and its homologues (see Table 2).…”
Section: Gene Expression Profiling Of Fibroblastsmentioning
confidence: 99%
“…14 Despite significant investigation, a complete picture of the molecular mediators of epithelial-nonparenchymal interaction in hepatocyte cocultures is unavailable. To date, the data suggest that both matrix deposition 15,16 and direct cell-cell contact play a role 10,17,18 in the "coculture effect," whereas soluble factors have proven to be largely ineffective. 14,19,20 Two promising candidate cell surface proteins are epithelial cadherin (E-cadherin) 17 and liverregulating protein 9 ; however, NPCs lacking E-cadherin and liver-regulating protein retain the ability to support hepatic functions, suggesting that neither is the sole mediator of the "coculture effect."…”
mentioning
confidence: 99%
“…Moreover, other cells have been effective, including both liver endothelial cells and nonhepatic cells (145)(146)(147). Studies from our laboratory (148,149) have shown that the presence of an integral plasma membrane glycoprotein is a prerequisite to obtain longterm survival of differentiated hepatocytes in coculture. This glycoprotein is expressed by both hepatocytes and rat liver epithelial cells and is also found in some other tissues (148,149).…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%
“…Studies from our laboratory (148,149) have shown that the presence of an integral plasma membrane glycoprotein is a prerequisite to obtain longterm survival of differentiated hepatocytes in coculture. This glycoprotein is expressed by both hepatocytes and rat liver epithelial cells and is also found in some other tissues (148,149). One could postulate that nonhepatic cells that express this glycoprotein are potentially capable of interacting with hepatocytes.…”
Section: However Survival and Metabolic Compe-mentioning
confidence: 99%